1990
DOI: 10.1091/mbc.1.7.511
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor alpha and a PC12-derived growth factor induce neurites in PC12 cells and enhance the survival of embryonic brain neurons.

Abstract: We have identified and characterized a 5000-Da protein that induces neurite outgrowth from PC12 pheochromocytoma cells, enhances the survival of embryonic rat brain neurons in primary culture, and induces the multiplication of embryonic rat brain astrocytes in primary culture. The factor is produced by a flat cell PC12 variant that expresses the activated ras oncogene after transfection of the gene. The factor resembles transforming growth factor alpha (TGF alpha) and epidermal growth factor (EGF) in that it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1993
1993
1997
1997

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…The role of the receptor autophosphorylation in EGF-induced signal transduction is not clear (e.g., Lichtner et al, 1992). Several serine and threonine residues of the receptor also become phosphorylated under various conditions and such phosphorylation can reduce the receptor tyrosine kinase activity (Schlessinger, 1988;Yarden and Ullrich, 1988;Carpenter and Cohen, 1990), Zhang et al (1990) reported that transforming growth factor-a (TGF-a), which also acts via the EGF receptor, induced the neuronal differentiation of PC12 pheochromocytoma cells in that it caused the cells to extend short neurites; EGF was found to produce a morphologically similar effect by these authors. Recently, Sano and Kitajima (1992) and Nakafuku and Kaziro (1993) also reported that EGF induces short neurites in PC12 cells.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The role of the receptor autophosphorylation in EGF-induced signal transduction is not clear (e.g., Lichtner et al, 1992). Several serine and threonine residues of the receptor also become phosphorylated under various conditions and such phosphorylation can reduce the receptor tyrosine kinase activity (Schlessinger, 1988;Yarden and Ullrich, 1988;Carpenter and Cohen, 1990), Zhang et al (1990) reported that transforming growth factor-a (TGF-a), which also acts via the EGF receptor, induced the neuronal differentiation of PC12 pheochromocytoma cells in that it caused the cells to extend short neurites; EGF was found to produce a morphologically similar effect by these authors. Recently, Sano and Kitajima (1992) and Nakafuku and Kaziro (1993) also reported that EGF induces short neurites in PC12 cells.…”
Section: Introductionmentioning
confidence: 94%
“…The ability of EGF to induce even short neurites in PC12 (Zhang et al, 1990;Sano and Kitajima, 1992;Nakafuku and Kaziro, 1993) is something of a surprise because others have reported that PC 12 cells respond to EGF but not by neurite outgrowth (Huff and Guroff, 1979;Chandler and Henchman, 1980;Boonstra et a]., 1983). This apparent discrepancy was ascribed to differences in the PC12 cell lines used (Zhang et al, 1990) or culture conditions (Nakafuku and Kaziro, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EGF and TGFa have been shown to induce process outgrowth and enhance cell survival in primary cultures of postmitotic neurons from a variety of brain areas (Morrison et al, 1987(Morrison et al, , 1988Abe et al, 1990;Kornblum et al, 1990;Zhang et al, 1990). Additionally, the presence of EGF in culture media can influence the expression of region-specific markers in cortical neurons in vitro (Ferri and Levitt, 1995).…”
Section: Potential Functions Of Egf-rmentioning
confidence: 99%
“…Indeed, numerous studies in vitro have supported these conclusions. Both EGF and TGFa influence the survival and differentiation of postmitotic CNS neurons in a variety of systems, including neurons derived from the postnatal basal ganglia (Morrison et al, 1987), from embryonic and postnatal neocortex (Abe et al, 1990;Zhang et al, 1990;Kornblum et al, 1990) and dopaminergic neurons from embryonic midbrain (Casper et al, 1991;Alexi and Hefti, 1993). EGF and TGFa have also been shown to induce the proliferation of cultured CNS astrocytes (Leutz and Schachner, 1981), as well as to influence oligodendrocyte differentiation (Almazan et al, 1985;Sheng et al, 1989).…”
mentioning
confidence: 99%